Natural analogue evidence for controls on radionuclide uptake by fractured crystalline rock. (January 2021) - Metcalfe, Richard; Milodowski, Antoni E.; Field, Lorraine P.; Wogelius, Roy A.; Carpenter, Gráinne; Yardley, Bruce W.D.; Norris, Simon
Abstract: Fractured Crystalline Rocks (FCR) are being considered in several countries as hosts for radioactive waste repositories. In FCR, radionuclides may be transported relatively rapidly by bulk groundwater flow through open fractures, but much more slowly by diffusion through porewater in the rock matrices. Rock matrix diffusion (RMD) is the diffusion of radionuclides in the aqueous phase, between open fractures and rock matrices. Sorption or co-precipitation on the fracture surfaces and walls of the matrix pores causes further radionuclide retardation. RMD may be important in a repository's safety case and has been investigated by many published short-term (to a few years) laboratory and in-situ experiments. To improve understanding over longer timescales, we investigated evidence for RMD of several natural radioelements, and radioelement analogues, in five exemplar fractured crystalline rock (FCR) samples aged between c. 70 Ma and c. 455 Ma. The sample suite consisted of two samples of Borrowdale Volcanic Group (BVG) meta-tuff from northwest England, a sample of Carnmenellis Granite from southwest England and two samples of Toki Granite from central Japan. Uptake or loss of the studied elements is limited to an altered damage zone in each sample, coupled to mineral alteration processes. These zones are most extensive (a few tens of millimetres) in the Toki Granite samples. We also found unstable primary igneous minerals to persist in the immediate wallrocks of fractures in studied granite samples, suggesting that pores were not permanently water saturated in these samples. Although only a small sample suite was studied, the results show that while RMD may be important in some kinds of FCR, in others it may be negligible. Site-specific information is therefore needed to determine how much reliance can be placed on RMD when developing a safety case. Graphical abstract: Image 1 Highlights: Fractured crystalline rock is often a candidate radioactive waste repository host. Radionuclide uptake by the rock can be important in a repository's safety case. Natural analogue studies of radionuclide uptake complement lab studies. Contrasting kinds of natural fractured crystalline rocks have been studied. Different kinds of fractured crystalline rocks have different uptake capabilities.